Висновок спеціаліста у кримінальному судочинстві - Бєлік, Лариса Степанівна; Бєлік, Л. С.; Белик, Лариса Степановна; Bielik, Larysa S. (Київ : Видавництво Ліра-К, 2022)
Стаття присвячена аспектам сучасного законодавчого регламентування підстав та вимог оформлення висновку спеціаліста у кримінальному судочинстві. Проаналізовано наукові праці видатних вітчизняних та іноземних вчених. Досліджено статті Кримінального процесуального кодексу України стосовно вимог до складання письмового висновку спеціаліста, щодо відповідальності експерта та спеціаліста за внесення неправдивих відомостей до висновку, й визначено межі виникнення такої відповідальності.

The article is devoted to the issues of modern legislative regulation regarding the grounds and requirements for the execution of a conclusion by a specialist in criminal proceedings. The scientific works of outstanding domestic and foreign scientists are analyzed and their great contribution to the study of this topic is indicated. Since they conduct a fundamental analysis of the domestic and foreign heritage on this issue, they help to determine the further debatable direction and carry out the subsequent scientific search. Articles of the Criminal Procedure Code of Ukraine and the Criminal Code of Ukraine regarding the requirements for drawing up a written conclusion of a specialist, as well as articles on the responsibility of an expert and a specialist for introducing false information into the conclusion of the study prepared by them, have been carefully researched and analyzed, and the boundaries of the emergence of a certain responsibility are indicated. It is indicated that the expert's conclusion as one of the sources of evidence in the case allows, at the appropriate scientific level, to objectively and fully solve the designated tasks that require the use of special knowledge. The norms of the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine in connection with the adoption of the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine on Simplification of Pre-trial Investigation of Certain Categories of Criminal Offenses” are analyzed. It is indicated that a written conclusion of a specialist can be obtained to clarify the circumstances of the commission of a criminal offense before entering information into the Unified Register of Pre-trial Investigations. It is also indicated that the conclusion of a specialist is recognized as a procedural source of evidence in criminal proceedings on criminal offenses with the proviso that such a procedural source of evidence cannot be used in criminal proceedings for a crime, except on the basis of a ruling by an investigating judge, which is issued at the request of the prosecutor. A comparative analysis was carried out regarding the content of the conclusions of the expert with the conclusions of the specialist. The general and distinctive positions in the written content of the conclusions of a specialist and an expert are indicated.
Бєлік Л. С. Висновок спеціаліста у кримінальному судочинстві / Л. С. Бєлік // Криміналістика і судова експертиза: міжвідом. наук.-метод. зб. / Київський НДІ судових експертиз; редкол.: Д. В. Журавльов (голов, ред.), О. Г. Рувін (заст. голов, ред.) та ін. - Київ : Видавництво Ліра-К, 2022. - Вил. 67. - С. 51-56.
Keywords: спеціаліст; експерт; висновок спеціаліста; висновок експерта; кримінальне правопорушення; specialist; expert; the conclusion of a specialist; the conclusion of an expert; criminal offense; Research Subject Categories::LAW/JURISPRUDENCE